Endoscopic Submucosal Dissection, a New Technique for en Bloc Resection of Large Superficial Tumor in the Esophagus - Nishimura, Makoto; Sakaguchi, Masafumi; Kitada, Hideki; Hifumi, Michio; Kita, Hiroto (IntechOpen, 2011)
None